Cobalt(II)/TPPMS‐Catalyzed Dehydrative Nucleophilic Substitution of Alcohols in Water. Issue 3 (22nd December 2016) - Hikawa, Hidemasa; Ijichi, Yukiko; Kikkawa, Shoko; Azumaya, Isao
Abstract : A green and sustainable direct dehydrative amination of alcohols, catalyzed by cobalt(II)/TPPMS (sodium diphenylphosphinobenzene‐3‐sulfonate) in water, is described. Earth‐abundant cobalt is used in form of Co(hfac)2 · x H2 O (hfac: hexafluoroacetylacetone), which acts as a highly efficient Lewis acidic catalyst. This simple atom‐economical protocol features mild conditions without the need for a base or other additives and affords the corresponding benzylic and allylic anilines along with water as the only coproduct. Mechanistic studies suggest that this system is driven by direct nucleophilic substitution of alcohols. Abstract : A green and sustainable direct dehydrative amination of alcohols, catalyzed by cobalt(II)/TPPMS (sodium diphenylphosphinobenzene‐3‐sulfonate) in water, is described.